2018
DOI: 10.12688/f1000research.13511.2
|View full text |Cite
|
Sign up to set email alerts
|

netSmooth: Network-smoothing based imputation for single cell RNA-seq

Abstract: Single cell RNA-seq (scRNA-seq) experiments suffer from a range of characteristic technical biases, such as dropouts (zero or near zero counts) and high variance. Current analysis methods rely on imputing missing values by various means of local averaging or regression, often amplifying biases inherent in the data. We present netSmooth, a network-diffusion based method that uses priors for the covariance structure of gene expression profiles on scRNA-seq experiments in order to smooth expression values. We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Finally, we investigated the usefulness for CRC subtyping of using prior information from protein interaction networks. Several groups, including our own, have previously incorporated gene–gene interactions using a method called network smoothing (26, 27). This is accomplished by allowing binary mutation values to diffuse over a gene network, a process which assigns nonzero “mutation scores” rather than binary mutation values, to genes which either have mutations or interact with mutated genes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, we investigated the usefulness for CRC subtyping of using prior information from protein interaction networks. Several groups, including our own, have previously incorporated gene–gene interactions using a method called network smoothing (26, 27). This is accomplished by allowing binary mutation values to diffuse over a gene network, a process which assigns nonzero “mutation scores” rather than binary mutation values, to genes which either have mutations or interact with mutated genes.…”
Section: Resultsmentioning
confidence: 99%
“…To carry this out, we used a gene network defining interactions between genes from the STRING db (28), a database of protein–protein interactions. We applied the netSmooth (27) algorithm (see the Materials and Methods section) to the mutation data before passing it to maui and computed Harrell’s c-index, as above. This revealed that network smoothing mutations further improve the clinical relevance of latent factors learned when integrating multiomics data (c = 0.79) (Fig 1G).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations